A high-fluidity epoxy resin encapsulation bottom filling glue and preparation method thereof

Through technical means such as compounding epoxy resin composition and modified filler, the problems of poor fluidity and insufficient performance of traditional filler glue are solved, and the underfill glue with high fluidity, rapid curing and excellent performance are achieved, which is suitable for complex packaging structures.

CN119161839BActive Publication Date: 2025-03-07SHANDONG HIGHDEV NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411688640.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

In actual application, traditional two-component epoxy resin underfill glue has problems such as difficult to control the mixing ratio, long curing time, and poor fluidity, which is difficult to meet the high requirements of advanced packaging technology for the performance of filling glue.

Method used

The underfill glue is encapsulated with high-flow epoxy resin, and the optimized molecular chain system is formed by combining components such as epoxy resin composition, modified fillers and coupling agents to improve mechanical and mechanical properties and flow properties, while maintaining excellent moisture-proof, water-proof, corrosion-proof and acid-base-resistant properties.

Benefits of technology

The high flowability, rapid curing, excellent mechanical properties and durability of the filler are achieved, adapting to the needs of complex packaging structures, and significantly improving the application performance of the filler.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of filling glue, and in particular to a high-flowability epoxy resin encapsulated bottom filling glue and a preparation method thereof. The high-flowability epoxy resin encapsulated bottom filling glue, in parts by mass, has the following raw materials: 40 to 60 parts of epoxy resin composition, 10 to 15 parts of active diluent, 20 to 25 parts of curing agent, 1 to 2 parts of accelerator, 20 to 35 parts of modified filler, 1 to 4 parts of coupling agent, 1 to 1.5 parts of leveling agent, and 1 to 3 parts of flame retardant. The epoxy resin encapsulated bottom filling glue prepared in the present application not only has good stress impact resistance, mechanical properties and flow properties, but also can maintain excellent moisture resistance, water resistance, corrosion resistance, acid and alkali resistance and other properties, thereby greatly improving the application performance of the filling glue and having very excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of filling glue, and in particular to a high-fluidity epoxy resin encapsulation bottom filling glue and a preparation method thereof. Background Art

[0002] As the trend of miniaturization and high performance of electronic devices becomes increasingly obvious, the requirements for packaging technology are also getting higher and higher. Especially in advanced packaging technologies such as flip chip and ball grid array (BGA), in order to improve the connection reliability and durability between the chip and the substrate, the use of underfill has become an important process step. The main function of underfill is to fill the gap between the chip and the substrate through capillary action, thereby reducing thermal stress, improving mechanical strength, and enhancing moisture and corrosion resistance.

[0003] Traditional bottom fillers mostly use two-component epoxy resin systems. Although this material has good bonding properties and heat resistance, it has some limitations in practical applications, such as difficult to control the mixing ratio, long curing time, and poor fluidity. In recent years, with the advancement of technology, single-component high-fluidity epoxy resin encapsulation bottom fillers have gradually become a research hotspot. This type of glue not only simplifies the use process and improves production efficiency, but also has better fluidity and faster curing speed while ensuring good physical and chemical properties, and can adapt to more complex packaging structures. Summary of the invention

[0004] In order to better solve the above problems, the present application provides a high-flowability epoxy resin encapsulation bottom filling glue and a preparation method thereof. The prepared epoxy resin encapsulation bottom filling glue not only has good stress impact resistance, mechanical properties and flow properties, but also can maintain excellent moisture-proof, water-resistant, corrosion-resistant, acid-resistant and alkali-resistant properties, thereby greatly improving the application performance of the filling glue and having a very excellent application prospect.

[0005] The first aspect of the present application provides a high-flowability epoxy resin encapsulation bottom filling glue, which comprises the following raw materials, in parts by mass: 40 to 60 parts of epoxy resin composition, 10 to 15 parts of active diluent, 20 to 25 parts of curing agent, 1 to 2 parts of accelerator, 20 to 35 parts of modified filler, 1 to 4 parts of coupling agent, 1 to 1.5 parts of leveling agent, and 1 to 3 parts of flame retardant.

[0006] As a preferred solution, the mass ratio of the epoxy resin composition, the modified filler and the coupling agent is 45-55:25-30:1.5-3.

[0007] As a preferred solution, the mass ratio of the epoxy resin composition, the modified filler and the coupling agent is 50-54:26-28:2-2.5.

[0008] As a preferred solution, the epoxy resin composition is a composition of bisphenol A epoxy resin, modified epoxy resin and epoxy block resin.

[0009] As a preferred solution, the mass ratio of the bisphenol A epoxy resin, the modified epoxy resin and the epoxy block resin is 35-40:5-10:3-6.

[0010] As a preferred solution, the mass ratio of the bisphenol A epoxy resin, the modified epoxy resin and the epoxy block resin is 38-40:8-10:4-5.

[0011] As a preferred solution, the epoxy equivalent of the bisphenol A epoxy resin is 180-200 g / eq.

[0012] As a preferred solution, the viscosity of the bisphenol A epoxy resin is 10000-15000 mPa·s at 25°C.

[0013] As a preferred scheme, the preparation method of the modified epoxy resin comprises the following steps: S1: heating bisphenol F epoxy resin to 80-90°C, then stirring at a speed of 120-150rpm and adding dodecyl glycidyl ether and glycidyl acrylate, stirring and mixing evenly; S2: adding hexamethylenediamine, benzyldimethylamine and N,N-dimethylbenzylamine, heating to 110-130°C, and keeping the temperature for reaction for 5-8h; S3: after the reaction is completed, naturally cooling to room temperature, pouring the product into a vacuum degassing machine, evacuating to -0.1 MPa, and maintaining for 10-15min, the product is obtained after completion.

[0014] As a preferred solution, the viscosity of the bisphenol F epoxy resin is 4500-6000 mPa·s at 25°C.

[0015] As a preferred solution, the mass ratio of the bisphenol F epoxy resin, dodecyl glycidyl ether and glycidyl acrylate is 8-10:2-4:1-2.

[0016] As a preferred solution, the mass ratio of hexamethylenediamine, benzyldimethylamine and N,N-dimethylbenzylamine is 1-2:0.4-0.8:0.2-0.4.

[0017] As a preferred solution, the epoxy block resin is a block copolymer of ethylene oxide-propylene oxide.

[0018] As a preferred solution, the weight average molecular weight of the epoxy block resin is 7000-10000 Da.

[0019] In this application, the addition of the compounded epoxy resin composition can effectively improve the mechanical properties of the filling glue, while maintaining good moisture-proof, water-resistant, corrosion-resistant, and aging-resistant properties. The combination of the added modified epoxy resin and epoxy block resin can form a good synergistic effect to improve the molecular chain system of the bisphenol A epoxy resin; the addition of the modified epoxy resin can not only enhance the interaction between the molecular chains in the bisphenol A epoxy resin system through the entanglement effect of its long chain branches, but also greatly improve the entanglement strength between the molecular chain segments, thereby greatly improving the intermolecular density in the internal resin system, greatly enhancing the intermolecular interaction force, and improving the cohesion of the system. At the same time, it can effectively reduce the penetration rate of water molecules inside the system, increase the free resistance of water molecules and active groups, and then improve the While maintaining high mechanical properties, it also maintains excellent moisture and water resistance; on the other hand, the addition of epoxy block resin can form an interfacial film layer with good compatibility in the resin system. The presence of this film layer can effectively help improve the barrier force for active groups and water molecules while preventing excessive liberation of the modified fillers dispersed inside, thereby achieving uniform dispersion of the modified fillers, thereby maintaining good system stability during long-term use, improving aging resistance, and further reducing the segregation and separation of internal particles, reducing the contact probability of internal active molecules, and thus having excellent corrosion resistance and aging resistance.

[0020] As a preferred solution, the active diluent is at least one of 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate, 1,4-butanediol diglycidyl ether, diethylene glycol diglycidyl ether, and phenyl glycidyl ether.

[0021] As a preferred solution, the active diluent is 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate.

[0022] As a preferred solution, the curing agent is at least one of hexahydrophthalic anhydride, dicyclopentadiene dianhydride, maleic anhydride and phthalic anhydride.

[0023] As a preferred solution, the curing agent is a composition of maleic anhydride and tricarboxylic anhydride.

[0024] As a preferred solution, the mass ratio of maleic anhydride to tricenhydride is 5-6:1-1.5.

[0025] As a preferred solution, the accelerator is at least one of 2-ethyl-4-methylimidazole, 2-methylimidazole, triethylamine, triethanolamine and benzotriazole.

[0026] As a preferred solution, the accelerator is 2-ethyl-4-methylimidazole.

[0027] As a preferred scheme, the preparation method of the modified filler includes the following steps: S1: adding silicon dioxide to DMF, then adding 3-aminopropyltriethoxysilane and glutaric anhydride, heating to 65-75°C, keeping warm for reaction for 2-3 hours, centrifugally filtering and drying after completion to obtain pretreated particles; S2: mixing the pretreated particles with ferric chloride hexahydrate and adding them to the DMF solution, stirring and mixing evenly, heating to 100-130°C, adding dropwise the DMF solution of 2-aminoterephthalic acid for 2-3 hours, and continuing to keep warm for reaction for 8-10 hours after the addition is completed; S3: cooling naturally to room temperature after the reaction is completed, centrifuging the product, washing it alternately with DMF and deionized water for 3-4 times, and finally vacuum drying it at 70-80°C for 10-12 hours, and obtaining it after completion.

[0028] As a preferred solution, the average particle size of the silicon dioxide is 15-25 nm.

[0029] As a preferred solution, the mass ratio of the silicon dioxide, 3-aminopropyltriethoxysilane and glutaric anhydride is 3-4:0.5-1:1.2-1.5.

[0030] As a preferred solution, the mass ratio of the pretreated particles, ferric chloride hexahydrate and 2-aminoterephthalic acid is 2-2.5:4-4.5:2.5-3.

[0031] As a preferred solution, the average particle size of the modified filler is 620-750 nm.

[0032] The modified filler added in the present application can not only greatly enhance its dispersion stability in the resin through the action of the surfactant group and the resin system group, but also play an internal supporting and connecting role when subjected to external force through the interaction force; on the other hand, the encapsulation structure formed by the modified filler particles can guide trace water molecules inside the resin, and then realize internal adsorption and removal of water molecules through the pores of its internal framework particles, thereby greatly improving the penetration resistance and penetration path of water molecules, thereby achieving a double improvement in mechanical properties and moisture-proof and water-resistant properties; on the other hand, the modified particles can greatly reduce the pore size of the storage micropores of the filler particles inside the resin system through their own good system connectivity, reduce the shaking and free phenomenon of the particles inside, and thus avoid the negative impact of the continuous expansion of pores on the corrosion resistance and aging resistance during long-term use.

[0033] As a preferred solution, the coupling agent is a silane coupling agent.

[0034] As a preferred solution, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and β-mercaptoethyltrimethoxysilane.

[0035] As a preferred solution, the leveling agent is polydimethylsiloxane.

[0036] As a preferred solution, the flame retardant is at least one of decabromodiphenyl ether, decabromodiphenyl ethane, triphenyl phosphate, trimethyl phosphate, ammonium polyphosphate, aluminum hydroxide, and zinc borate.

[0037] As a preferred solution, the flame retardant is decabromodiphenyl ether.

[0038] The second aspect of the present application provides a method for preparing the above-mentioned high-flowability epoxy resin encapsulation bottom filling glue, which specifically includes the following steps: S1: mixing the epoxy resin composition and the active diluent, stirring at a speed of 600~800rpm for 30~40min until mixed evenly to obtain a mixture; S2: adding a curing agent and an accelerator to the mixture and continuing to stir at a speed of 600~800rpm for 15~20min to fully dissolve them; S3: slowly adding the modified filler and the coupling agent to the mixture, stirring at a high speed of 1000~1500 rpm for 40~50min to evenly disperse them in the system; S4: finally adding a leveling agent and a flame retardant, stirring at a speed of 600~800rpm for 10~15min, and finally ensuring that all the ingredients are evenly mixed, pouring the mixed glue into a vacuum degassing machine, evacuating to -0.1 MPa, maintaining for 10~15min, removing bubbles generated during the mixing process, and sealing and storing after completion.

[0039] The beneficial effects of this application are:

[0040] 1. A high-flowability epoxy resin encapsulation bottom filling glue provided in the present application, the epoxy resin encapsulation bottom filling glue prepared therefrom not only has good stress impact resistance, mechanical properties and flow properties, but also can maintain excellent moisture-proof, water-resistant, corrosion-resistant, acid-resistant and alkali-resistant properties, thereby greatly improving the application performance of the filling glue, and has a very beneficial application prospect.

[0041] 2. A high-flowability epoxy resin encapsulation bottom filling glue provided in the present application can effectively improve the mechanical properties of the filling glue by adding a compounded epoxy resin composition, and at the same time maintain good moisture-proof, water-resistant, corrosion-resistant and aging-resistant properties; the combination of the added modified epoxy resin and epoxy block resin can form a good synergistic effect to improve the molecular chain system of bisphenol A epoxy resin; the addition of modified epoxy resin can not only enhance the interaction between molecular chains in the bisphenol A epoxy resin system through the entanglement effect of its long side chains, but also greatly improve the entanglement strength between molecular chain segments, thereby greatly improving the intermolecular density in the internal resin system, greatly enhancing the intermolecular interaction force, and improving the cohesion of the system. At the same time, it can effectively reduce the penetration rate of water molecules inside the system, increase the free resistance of water molecules and the free resistance of active groups, thereby maintaining excellent moisture-proof and water-resistant properties while improving the mechanical properties.

[0042] 3. A high-flowability epoxy resin encapsulation bottom filling glue provided in the present application, the added modified filler can not only greatly enhance its dispersion stability in the resin through the action of the surfactant group and the resin system group, but also play an internal supporting and connecting role when subjected to external force through the interaction force; on the other hand, the encapsulation structure formed by the modified filler particles can achieve a guiding effect on trace water molecules inside the resin, and then achieve internal adsorption and removal of water molecules through the pores of its internal framework particles, thereby greatly improving the penetration resistance and penetration path of water molecules, thereby achieving a double improvement in mechanical properties and moisture-proof and water-resistant properties; on the other hand, the modified particles can greatly reduce the pore size of the storage micropores of the filler particles inside the resin system through their own good system connectivity, reduce the shaking and free phenomenon of the particles inside, and thus avoid the negative impact of the continuous expansion of the pores on the corrosion resistance and aging resistance during long-term use. DETAILED DESCRIPTION

[0043] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0044] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0045] Example 1

[0046] Example 1 The first aspect provides a high-flowability epoxy resin encapsulation bottom filling glue, the raw materials are, by mass: 52.5 parts of epoxy resin composition, 12.6 parts of active diluent, 23.4 parts of curing agent, 1.5 parts of accelerator, 27.5 parts of modified filler, 2.2 parts of coupling agent, 1.3 parts of leveling agent, and 1.2 parts of flame retardant.

[0047] The epoxy resin composition is a composition of bisphenol A epoxy resin, modified epoxy resin and epoxy block resin, and the mass ratio of the three is 39:9:4.5.

[0048] The bisphenol A epoxy resin was purchased from the Epon828 product sold by Hanson, USA, with an epoxy equivalent of 192 g / eq and a viscosity of 12000 mPa·s at 25°C.

[0049] The preparation method of modified epoxy resin includes the following steps, calculated by mass: S1: 9.5 parts of bisphenol F epoxy resin are heated to 85°C, then stirred at a speed of 120 rpm and 2.8 parts of dodecyl glycidyl ether and 1.2 parts of glycidyl acrylate are added, and stirred to mix evenly; S2: 1.3 parts of hexamethylenediamine, 0.6 parts of benzyldimethylamine and 0.3 parts of N,N-dimethylbenzylamine are added, the temperature is raised to 120°C, and the reaction is kept warm for 6 hours; S3: after the reaction is completed, it is naturally cooled to room temperature, the product is poured into a vacuum degassing machine, vacuumed to -0.1 MPa, and maintained for 12 minutes, and the product is obtained after completion.

[0050] Bisphenol F epoxy resin was purchased from Shandong Polychemical Co., Ltd., China, and its viscosity was 5000 mPa·s at 25°C.

[0051] The epoxy block resin is a block copolymer of ethylene oxide-propylene oxide, with a weight average molecular weight of 7800 Da, and is purchased from L series ethylene oxide-propylene oxide block copolymer products of corresponding molecular weight sold by BASF, Germany.

[0052] The active diluent is 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate.

[0053] The curing agent is a composition of maleic anhydride and tricarboxylic anhydride, and the mass ratio of the two is 5.6:1.3.

[0054] The accelerator is 2-ethyl-4-methylimidazole.

[0055] The preparation method of the modified filler includes the following steps, calculated by mass: S1: adding 3.2 parts of silicon dioxide to 100 parts of DMF, then adding 0.6 parts of 3-aminopropyltriethoxysilane and 1.4 parts of glutaric anhydride, heating to 70°C, keeping warm for reaction for 3 hours, centrifugally filtering and drying after completion to obtain pretreated particles; S2: mixing 2.2 parts of pretreated particles with 4.3 parts of ferric chloride hexahydrate and adding them to 160 parts of DMF solution, stirring and mixing evenly, heating to 120°C, and dropwise adding 40 parts of DMF solution containing 2.8 parts of 2-aminoterephthalic acid, the dropping time is 2.5 hours, and after the dropping is completed, the heat preservation reaction is continued for 8 hours; S3: after the reaction is completed, it is naturally cooled to room temperature, the product is centrifuged, washed alternately with DMF and deionized water for 3 times, and finally vacuum dried at 80°C for 10 hours, and the product is obtained after completion.

[0056] The average particle size of silica is 20 nm.

[0057] The average particle size of the modified filler is 660 nm.

[0058] The coupling agent is γ-aminopropyltriethoxysilane.

[0059] The leveling agent is polydimethylsiloxane DC-200.

[0060] The flame retardant is decabromodiphenyl ether.

[0061] The second aspect of the present embodiment provides a method for preparing the above-mentioned high-flowability epoxy resin encapsulation bottom filling glue, which specifically includes the following steps: S1: mixing the epoxy resin composition and the active diluent, stirring at a speed of 800 rpm for 40 minutes until the mixture is uniformly mixed to obtain a mixture; S2: adding a curing agent and an accelerator to the mixture and continuing to stir at a speed of 800 rpm for 20 minutes to fully dissolve them; S3: slowly adding the modified filler and the coupling agent to the mixture, stirring at a high speed of 1200 rpm for 45 minutes to uniformly disperse them in the system; S4: finally adding a leveling agent and a flame retardant, stirring at a speed of 600 rpm for 10 minutes, and finally ensuring that all the ingredients are evenly mixed, pouring the mixed glue into a vacuum degassing machine, evacuating to -0.1 MPa, maintaining for 12 minutes, removing bubbles generated during the mixing process, and sealing and storing after completion.

[0062] Example 2

[0063] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the high-flowability epoxy resin encapsulation bottom filling glue, in parts by mass, are: 45.5 parts of epoxy resin composition, 10 parts of active diluent, 22.1 parts of curing agent, 1.2 parts of accelerator, 29.6 parts of modified filler, 1.6 parts of coupling agent, 1.3 parts of leveling agent, and 1.2 parts of flame retardant.

[0064] Example 3

[0065] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the high-flowability epoxy resin encapsulation bottom filling glue, in parts by mass, are: 55 parts of epoxy resin composition, 14 parts of active diluent, 24.5 parts of curing agent, 1.6 parts of accelerator, 25 parts of modified filler, 2.8 parts of coupling agent, 1.3 parts of leveling agent, and 1.2 parts of flame retardant.

[0066] Comparative Example 1

[0067] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the high-flowability epoxy resin encapsulation bottom filling glue, in parts by mass, are: 75 parts of epoxy resin composition, 21.5 parts of active diluent, 23.4 parts of curing agent, 1.5 parts of accelerator, 15.5 parts of modified filler, 1 part of coupling agent, 1.3 parts of leveling agent, and 1.2 parts of flame retardant.

[0068] Comparative Example 2

[0069] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the high-flowability epoxy resin encapsulation bottom filling glue, in parts by mass, are: 42.5 parts of epoxy resin composition, 12.6 parts of active diluent, 23.4 parts of curing agent, 1.5 parts of accelerator, 40.5 parts of modified filler, 2.2 parts of coupling agent, 1.3 parts of leveling agent, and 1.2 parts of flame retardant.

[0070] Comparative Example 3

[0071] The specific implementation of this comparative example is basically the same as that of Example 1, except that the epoxy resin composition is a composition of bisphenol A epoxy resin, modified epoxy resin and epoxy block resin, and the mass ratio of the three is 46:6:0.5.

[0072] Comparative Example 4

[0073] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being: The preparation method of the modified epoxy resin comprises the following steps, in parts by mass: S1: Heat 15.5 parts of bisphenol F epoxy resin to 85°C, then stir at 120rpm and add 1.2 parts of dodecyl glycidyl ether and 0.5 parts of glycidyl acrylate, and stir to mix evenly; S2: Add 1.3 parts of hexamethylenediamine, 0.6 parts of benzyldimethylamine and 0.3 parts of N,N-dimethylbenzylamine, raise the temperature to 120°C, and keep the reaction for 6 hours; S3: After the reaction is completed, naturally cool to room temperature, pour the product into a vacuum degassing machine, evacuate to -0.1 MPa, and keep for 12 minutes, and the product is obtained after completion.

[0074] Comparative Example 5

[0075] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified epoxy resin comprises the following steps, in parts by mass: S1: heat 5.5 parts of bisphenol F epoxy resin to 85°C, then stir at 120 rpm and add 4.5 parts of dodecyl glycidyl ether and 2 parts of glycidyl acrylate, and stir to mix evenly; S2: add 1.8 parts of hexamethylenediamine, 0.2 parts of benzyldimethylamine and 0.1 parts of N,N-dimethylbenzylamine, heat to 120°C, and keep warm for 6 hours; S3: after the reaction is completed, naturally cool to room temperature, pour the product into a vacuum degassing machine, evacuate to -0.1 MPa, and keep for 12 minutes, and the product is obtained after completion.

[0076] Comparative Example 6

[0077] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler includes the following steps, calculated by mass: S1: adding 4.5 parts of silicon dioxide to 60 parts of DMF, then adding 0.2 parts of 3-aminopropyltriethoxysilane and 0.6 parts of glutaric anhydride, heating to 70°C, keeping warm for reaction for 3 hours, centrifuging and drying after completion to obtain pretreated particles; S2: mixing 2.2 parts of pretreated particles with 4.3 parts of ferric chloride hexahydrate, adding them to 160 parts of DMF solution, stirring and mixing evenly, heating to 120°C, and adding dropwise 40 parts of DMF solution containing 2.8 parts of 2-aminoterephthalic acid, the dropping time is 2.5 hours, and the keeping warm for reaction is continued for 8 hours after the dropping is completed; S3: after the reaction is completed, naturally cool to room temperature, centrifuge the product, wash it alternately with DMF and deionized water for 3 times, and finally vacuum dry it at 80°C for 10 hours, and it is obtained after completion.

[0078] The average particle size of the modified filler is 540 nm.

[0079] Comparative Example 7

[0080] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler includes the following steps, calculated by mass: S1: adding 3.2 parts of silicon dioxide to 100 parts of DMF, then adding 0.6 parts of 3-aminopropyltriethoxysilane and 1.4 parts of glutaric anhydride, heating to 70°C, keeping warm for reaction for 3 hours, centrifugally filtering and drying after completion to obtain pretreated particles; S2: mixing 4.1 parts of pretreated particles with 4.3 parts of ferric chloride hexahydrate, adding them to 160 parts of DMF solution, stirring and mixing evenly, heating to 120°C, and adding dropwise 40 parts of DMF solution containing 2.8 parts of 2-aminoterephthalic acid, the dropping time is 2.5 hours, and the keeping warm for reaction is continued for 8 hours after the dropping is completed; S3: after the reaction is completed, naturally cool to room temperature, centrifuge the product, wash it alternately with DMF and deionized water for 3 times, and finally vacuum dry it at 80°C for 10 hours, and it is obtained after completion.

[0081] The average particle size of the modified filler is 860 nm.

[0082] Performance Evaluation

[0083] Mechanical property test: After curing, the filling glue prepared in the embodiment and the comparative example was subjected to a mechanical strength test. The thickness of the filling glue sample was 0.2 mm. The test was conducted in accordance with ASTM D638 standard. The measured values ​​were averaged over 10 tests and recorded in Table 1.

[0084] Waterproof test: After curing, the filling glue prepared in the embodiment and the comparative example was subjected to a hygroscopicity test. The thickness of the filling glue sample was 0.2 mm. The water absorption rate was tested according to the reference standard ASTM D570-98. The measured values ​​were averaged over 10 tests and recorded in Table 1.

[0085] Salt spray corrosion resistance test: The filling glue prepared in the embodiment and the comparative example was subjected to a salt spray corrosion resistance test after curing. The thickness of the filling glue sample was 0.2 mm, the test liquid was 5 wt% NaCl, the test temperature was 35±2°C, the test relative humidity was 95±2%, the spray sedimentation rate was 1.5 mL / 80cm² / h, and samples were taken and observed every 50 hours to record whether there was obvious corrosion, yellowing, blistering, or cracking. The test time when the above phenomena first appeared was recorded, and the results were recorded in Table 1.

[0086] Aging resistance test: After curing, the filling glue prepared in the embodiment and the comparative example was subjected to a salt spray corrosion resistance test. The thickness of the filling glue sample was 0.2 mm. The sample was placed in a constant temperature and humidity chamber at a temperature of 65±2°C and a relative humidity of 75±2%. It was stored for 3 months. After that, the sample was taken out and observed for obvious corrosion, damage, yellowing, blistering, and cracking. If there were any, it was recorded as unqualified, otherwise it was qualified. 50 groups of samples were tested in each group, and the qualified rate results were recorded in Table 1.

[0087] Table 1

[0088]

[0089] According to the examples and comparative examples and the data in Table 1, it can be known that by adopting the special technical solutions in the present application, examples 1 to 3 can obtain excellent waterproof, aging resistance, salt spray corrosion resistance and mechanical mechanical properties. This is the result of the combined action of the compounded epoxy resin composition and the modified filler and other technical solutions in the present application. The corresponding properties obtained make the coating have a very excellent market prospect. However, because comparative examples 1 to 7 do not adopt the special technical solutions, the overall performance of the coatings obtained is significantly worse than that of examples 1 to 3, which further proves that the technical effect of the technical solution adopted in the present application is not an obvious technical effect.

Claims

1. A high-flow epoxy resin encapsulation bottom filling glue, characterized by: The raw materials are as follows: 40-60 parts of epoxy resin composition, 10-15 parts of active diluent, 20-25 parts of curing agent, 1-2 parts of accelerator, 20-35 parts of modified filler, 1-4 parts of coupling agent, 1-1.5 parts of leveling agent, and 1-3 parts of flame retardant, in parts by mass; The epoxy resin composition is a composition of bisphenol A epoxy resin, modified epoxy resin and epoxy block resin; the mass ratio of the bisphenol A epoxy resin, modified epoxy resin and epoxy block resin is 35-40:5-10:3-6; Preparation method of modified epoxy resin The following steps are involved: S1: Heat bisphenol F epoxy resin to 80-90°C, then stir at 120-150rpm and add dodecyl glycidyl ether and glycidyl acrylate, stir and mix evenly; S2: Add hexamethylenediamine, benzyldimethylamine and N,N-dimethylbenzylamine, heat to 110-130°C, and keep warm for 5-8h; S3: After the reaction is completed, cool naturally to room temperature, pour the product into a vacuum degassing machine, evacuate to -0.1 MPa, keep for 10-15min, and obtain the product after completion; The viscosity of the bisphenol F epoxy resin is 4500-6000 mPa·s at 25° C.; The mass ratio of the bisphenol F epoxy resin, dodecyl glycidyl ether and glycidyl acrylate is 8-10:2-4:1-2; The mass ratio of hexamethylenediamine, benzyldimethylamine and N,N-dimethylbenzylamine is 1-2: 0.4-0.8: 0.2-0.4; The epoxy block resin is a block copolymer of ethylene oxide and propylene oxide; The weight average molecular weight of the epoxy block resin is 7000-10000Da; The preparation method of the modified filler comprises the following steps: S1: adding silicon dioxide to DMF, then adding 3-aminopropyltriethoxysilane and glutaric anhydride, heating to 65-75° C., keeping the temperature for 2-3 hours, centrifugally filtering and drying after completion to obtain pretreated particles; S2: Mix the pretreated particles and ferric chloride hexahydrate and add them to the DMF solution, stir and mix evenly, heat to 100-130°C, and dropwise add the DMF solution of 2-aminoterephthalic acid for 2-3 hours. After the dropwise addition is completed, continue to keep the temperature and react for 8-10 hours; S3: After the reaction is completed, naturally cool to room temperature, centrifuge the product, wash it alternately with DMF and deionized water for 3-4 times, and finally vacuum dry it at 70-80°C for 10-12 hours. After completion, the product is obtained; The average particle size of the silicon dioxide is 15 to 25 nm; The mass ratio of the silicon dioxide, 3-aminopropyltriethoxysilane and glutaric anhydride is 3-4:0.5-1:1.2-1.5; The mass ratio of the pretreated particles, ferric chloride hexahydrate and 2-aminoterephthalic acid is 2-2.5:4-4.5:2.5-3; The average particle size of the modified filler is 620-750 nm.

2. The high-flow epoxy resin encapsulation bottom filling adhesive according to claim 1, characterized in that: The mass ratio of the epoxy resin composition, the modified filler and the coupling agent is 45-55:25-30:1.5-3.

3. The high-flow epoxy resin encapsulation bottom filling adhesive according to claim 2, characterized in that: The epoxy equivalent of the bisphenol A epoxy resin is 180-200 g / eq.

4. The high-flow epoxy resin encapsulation bottom filling adhesive according to claim 3, characterized in that: The viscosity of the bisphenol A epoxy resin is 10000-15000 mPa·s at 25°C.

5. The high-flow epoxy resin encapsulation bottom filling adhesive according to claim 4, characterized in that: The active diluent is at least one of 3,4-epoxycyclohexyl methyl ester of 3,4-epoxycyclohexyl carboxylate, 1,4-butanediol diglycidyl ether, diethylene glycol diglycidyl ether, and phenyl glycidyl ether.

6. The high-flow epoxy resin encapsulation bottom filling adhesive according to claim 5, characterized in that: The curing agent is at least one of hexahydrophthalic anhydride, dicyclopentadiene dianhydride, maleic anhydride and phthalic anhydride.

7. The high-flow epoxy resin encapsulation bottom filling adhesive according to claim 6, characterized in that: The accelerator is at least one of 2-ethyl-4-methylimidazole, 2-methylimidazole, triethylamine, triethanolamine and benzotriazole.

8. A method for preparing the high-flow epoxy resin encapsulation bottom filling adhesive according to any one of claims 1 to 7, characterized in that: The specific steps include: S1: mixing the epoxy resin composition and the active diluent, stirring at a speed of 600-800 rpm for 30-40 minutes until the mixture is uniformly mixed to obtain a mixture; S2: adding a curing agent and an accelerator to the mixture and continuing to stir at a speed of 600-800 rpm for 15-20 minutes to fully dissolve them; S3: Slowly add the modified filler and coupling agent to the mixture, stir at a speed of 1000-1500 rpm for 40-50 minutes to evenly disperse them in the system; S4: Finally, add the leveling agent and flame retardant, stir at a speed of 600-800 rpm for 10-15 minutes, and finally ensure that all ingredients are evenly mixed, then pour the mixed glue into a vacuum degassing machine, evacuate to -0.1 MPa, maintain for 10-15 minutes, remove the bubbles generated during the mixing process, and seal and store after completion.

Citation Information

Patent Citations

  • Underfill adhesive and preparation method thereof

    CN104962224A

  • Underfill adhesive

    CN112724899A

Cited By

  • High-reliability underfill adhesive and preparation method thereof

    CN122255922A